2007
DOI: 10.1021/ef060314t
|View full text |Cite
|
Sign up to set email alerts
|

Change in Operational Characteristics of Diesel Engines Running on RME Biodiesel Fuel

Abstract: Complex research into the change of parameters concerning the fuel economy, thrust, and harmful components of exhaust gases, namely, hydrocarbons (HC), carbon monoxide (CO), and nitric oxides (NOx), was carried out to evaluate the efficiency of fuel replacement; that is, mineral diesel fuel, which is normally used by diesel engine fleets of agricultural machinery in Lithuania, was replaced with biofuel (hereafter biodiesel), which is rapeseed oil methyl esters, hereafter RME. Diesel engine F2L511 and a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 2 publications
1
15
0
8
Order By: Relevance
“…of biological origin fuel mixtures with fossil diesel fuel. is concentration was chosen taking into account a fact that foreign authors carried out tests on diesel engines (Lebedevas et al 2006a(Lebedevas et al , 2007 and found out that 30% of FAME mixture with D was of optimal concentration, in a view of improving diesel fuel economy and ecological indicators. e quality indicators of fatty acid methyl esters and their mixtures were evaluated applying the procedures speci ed in the standard LST EN 14214:2009. e physical and chemical parameters of the tested fuels (methyl ester mixtures with fossil diesel fuel) were determined applying standard methods:…”
Section: Fuel Used For Researchesmentioning
confidence: 99%
See 1 more Smart Citation
“…of biological origin fuel mixtures with fossil diesel fuel. is concentration was chosen taking into account a fact that foreign authors carried out tests on diesel engines (Lebedevas et al 2006a(Lebedevas et al , 2007 and found out that 30% of FAME mixture with D was of optimal concentration, in a view of improving diesel fuel economy and ecological indicators. e quality indicators of fatty acid methyl esters and their mixtures were evaluated applying the procedures speci ed in the standard LST EN 14214:2009. e physical and chemical parameters of the tested fuels (methyl ester mixtures with fossil diesel fuel) were determined applying standard methods:…”
Section: Fuel Used For Researchesmentioning
confidence: 99%
“…Producing and using biofuels has opened a new area in Lithuania as well as researches in this area (Matijošius and Sokolovskij 2009;Pukalskas et al 2009;Raslavičius and Bazaras 2009;Lebedevas and Lebedeva 2009;Pukalskas 2008a and2008b;Butkus et al 2007; Lebedevas et al 2007;Raslavičius and Markšaitis 2007;Lebedevas et al 2006aLebedevas et al , 2006b.…”
Section: Introductionmentioning
confidence: 99%
“…Th e expansion of production and the use of biofuels are determined by the legal acts of the European Commission and National legal acts encouraging such production and usage Producing and using biofuels has opened a new area in Lithuania as well as researches in this area (Matijošius and Sokolovskij 2009;Raslavičius and Bazaras 2009;Raslavičius 2009;Bazaras and Raslavičius 2008;Lebedevas and Lebedeva 2009;Pukalskas 2008a and2008b;Lebedevas et al 2007a and2007b;Raslavičius and Markšaitis 2007;Labeckas 2005;Makarevičienė 2005). …”
Section: Introductionmentioning
confidence: 99%
“…Introducing the oxygenated compounds such as rapeseed methyl ester and ethanol into diesel fuel is presently the best way to achieve the required results in case of pollution (see Table 1). Th us, as far as the exploitation of diesel engines fuelled with D/RME blends is well-known, the factfi ndings of the infl uence of ethanol additives on engine characteristics presented in the scientifi c papers are still discussed by many researchers (Shi et al 2005 andPągowski 2003;Lebedevas et al 2006Lebedevas et al , 2007Lebedevas et al and 2009Pikūnas et al 2006;Labeckas 2005;Hansen et al 2001;Raslavičius 2009;Raslavičius and Markšaitis 2007;Mittelbach and Remschmidt 2004;Kwanchareon et al 2007;Bazaras and Raslavičius 2008;Török 2009;Al-Hasan and Al-Momany 2008). Th ese facts have encouraged initiating research on the characteristics of the diesel engine fuelling it with blends consisting of mineral diesel and bio-based fuel additives.…”
Section: Introductionmentioning
confidence: 99%
“…Research results have paved the way to formulate a biofuel blend from renewable material that has energy values comparable to those of fossil fuels (Raslavičius 2009), superior lubricity (Kwanchareon et al 2007) and environmentally friendly characteristics (Shi et al 2005 andPągowski 2003;Lebedevas et al 2006 andHansen et al 2001;Raslavičius 2009;Kwanchareon et al 2007).…”
Section: Introductionmentioning
confidence: 99%